The National Anti-mafia Direction and the Anti-mafia Investigation Department: Giovanni Falcone’s vision (Rivista di Studi e Ricerche sulla criminalità organizzata, 2019)
This intervention aims to clarify the relationship between the idea of the National Anti-mafia Prosecutor's Office and the Anti-mafia Investigation Department drawn up by Giovanni Falcone and the subsequent developments of these fundamental structures of the fight against the mafia. The reference point is the hearing held by Giovanni Falcone in front of the Superior Council of the Judiciary in February 1992. In this context, the article enhances the impulse that Falcone himself gave to realize a world conference with the aim of promoting a multilateral cooperation in the struggle to organized crime.Keywords: Giovanni Falcone; National Anti-Mafia Direction; Anti-Mafia Investigation Department; coordination; judicial investigations; preventive investigations; aguidelines; supranational organized crime